Learning Environment and Learners Achievement in Mathematics: A Case Study of Selected Secondary Schools in Amolatar District. - Kanakulya, Fred (Kabale University, 2023)
Amolatar district has been struggling with poor performance in Mathematics for several years. The aim of this research is to determine how teacher competence, provision of good quality instructional materials and learners attitude, affect learning achievement in Mathematics among Ordinary level students in selected secondary schools of Amolatar District. With the overall goal of finding the combination of factors that can be targeted to improve performance. The findings showed that, 35% of the learners strongly agreed and 32% agreed to the fact that their teachers ask questions to see if they have understood the lesson content followed by 46% of the learners who strongly agreed that their Mathematics teachers help them in describing the lesson. Finally 39% also strongly agreed that their Mathematics teachers use practical examples on board. The adjusted R-square of 0.886 (88.6%) shows that there is a strong positive relationship between the learners’ scores and the three factors identified above. The study also found out that most of the teachers (47.1%) often use instructional materials when teaching Mathematics. The study concludes that provision of good quality instructional material improves students learning achievement. Therefore, the study recommends vigorous sensitization, seminars and career guidance to the students so as to improve their interest for positive attitude toward Mathematics.